Association between hepatitis C infection and number of screened blood unit transfusions in thalassemic children - Diah Asri Wulandari; Iesje Martiza; Yasmar Alfa; Dwi Prasetyo (Paediatrica Indonesiana, 2005)
Background Donor blood screening test for antibody againsthepatitis C virus (HCV) by third generation ELISA is widely used.However, there is still a window period during which a donor mayalready be infected despite a negative screening test.Objectives To determine the prevalence of hepatitis C infection inthalassemic children who had received screened donor blood andto seek the association between HCV infection and the number ofblood unit transfusions received.Methods This was an analytic cross-sectional study. Sixty-sevenchildren who had received third generation ELISA screened donorblood were examined for HCV antibody. The study was conductedin Hasan Sadikin General Hospital, Bandung, from January toMarch 2004. The prevalence of hepatitis C was presented in per-centage. The association between HCV infection and sex, age,interval between transfusions, and the number of blood unit trans-fusions received was determined by univariate analysis and logis-tic regression analysis.Results In univariate analysis, significant difference between HCV-infected and uninfected subjects was found in the mean age andmean number of blood units transfused (P<0.001). In logistic re-gression analysis, we found a significant association between thequantity of transfused blood with positive HCV antibody (P<0.001).The odds ratio for positive HCV antibody was 1.08 for each bloodunit transfusion received (95%CI 1.02;1.14). The prevalence ofhepatitis C in thalassemic children who received third generationELISA screened blood was 22.4% (95%CI 12.4%;32.4%). Thisprevalence is lower than that in a previous study of thalassemicchildren receiving unscreened blood (50.8%).Conclusions The prevalence of HCV infection in thalassemic chil-dren who had received screened donor blood is 22.4%. HCV in-fection is significantly associated with the number of screened bloodunit transfusions